2010
DOI: 10.1206/681.1
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Braincase in the Cretaceous Hybodont Shark Tribodus limae (Chondrichthyes: Elasmobranchii), Based on CT Scanning

Abstract: The braincase of the Lower Cretaceous hybodont shark Tribodus limae is examined using highresolution CT scanning, and its internal and external morphology is described based on threedimensional digital reconstructions. This study represents the first in-depth examination of a hybodont braincase using CT scanning and digital imaging technology. The braincase of an additional Lower Cretaceous hybodont, Egertonodus basanus, is also digitally reconstructed and compared to Tribodus. A reconstruction of cranial nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 31 publications
2
47
0
Order By: Relevance
“…In neoselachians and holocephalans the dorsal and lateral dorsal aortas are free below the neurocranium, whereas in some basal chondrichthyans the dorsal aorta is enclosed in the basicranial canal (for example, Cobelodus [39]) and in all basal chondrichthyans the lateral dorsal aortas run into the basicranial canals (for example, Cladodoides [37]). In addition, in neoselachians the posterior part of the basicranial arterial system forms a bell-shaped circuit due to the laterally curving position of the lateral dorsal aortas posteriorly and the V-shaped disposition of the internal carotid arteries anteriorly [79], whereas in basal chondrichthyans the basicranial circuit is narrower, more elongated and lacks the posterior bell-shaped curve. In recent holocephalans, as well as in some primitive holocephalans (for example, Iniopera [60]), the internal carotid arteries abort during ontogeny [5].…”
Section: Discussionmentioning
confidence: 99%
“…In neoselachians and holocephalans the dorsal and lateral dorsal aortas are free below the neurocranium, whereas in some basal chondrichthyans the dorsal aorta is enclosed in the basicranial canal (for example, Cobelodus [39]) and in all basal chondrichthyans the lateral dorsal aortas run into the basicranial canals (for example, Cladodoides [37]). In addition, in neoselachians the posterior part of the basicranial arterial system forms a bell-shaped circuit due to the laterally curving position of the lateral dorsal aortas posteriorly and the V-shaped disposition of the internal carotid arteries anteriorly [79], whereas in basal chondrichthyans the basicranial circuit is narrower, more elongated and lacks the posterior bell-shaped curve. In recent holocephalans, as well as in some primitive holocephalans (for example, Iniopera [60]), the internal carotid arteries abort during ontogeny [5].…”
Section: Discussionmentioning
confidence: 99%
“…X-ray CT has, however, been used to investigate the skulls of several Paleozoic and Mesozoic chondrichthyans (Pradel et al, 2009;Lane, 2010;Maisey & Lane, 2010;Fig. 3a), but investigations of the inner ear have often centered on morphological description, with an emphasis on resolving the systematics of the clades concerned.…”
Section: Nontetrapod Vertebratesmentioning
confidence: 99%
“…They found that phonoreception-related characters are present in Mesozoic . ca, ampulla for the caudal semicircular canal; ca, cochlear aqueduct; cc, cochlear canal; cscc, caudal semicircular canal; ds, dorsal sinus; fr, fenestra rotunda; fv, fenestra vestibuli; la, ampulla for the lateral semicircular canal; lscc, lateral semicircular canal; ra, ampulla for the rostral semicircular canal; rscc, rostral semicircular canal; sac, saccule; st, stapes; u, utricle hybodont sharks [Tribodus limae and Egertonodus basanus; see Lane (2010) for detailed description], but are absent from osteichthyans, living and extinct holocephalans, and some Paleozoic chondrichthyans, such as the Early Devonian Pucapampella (Maisey & Anderson, 2001). From this evidence Maisey and Lane (2010) concluded that the labyrinth of living elasmobranchs is highly specialized for low frequency semidirectional sound detection, and that the adaptation must have arisen only once in chondrichthyans some time after the split between elasmobranchs and chimeroids.…”
Section: Nontetrapod Vertebratesmentioning
confidence: 99%
“…While dismissed as a nomen dubium by some (Rees & Underwood, 2002), Werner (1990), Dutheil (1999), Lane (2010) & Cavin et al (2010 consider A. aegyptiacus valid and this opinion is accepted herein. Squatina sp (Dumeril, 1806;Slaughter & Thurmond, 1974;Underwood & Mitchel, 1999) is also known from Bahariya.…”
Section: Fishmentioning
confidence: 92%